Ar-Rahnu Scheme Among Low-Income Civil Servants in Malaysian Public Universities - Nurul Anith Farhana Mohd Indra; Kamarulzaman Ismail; Hasri Mustafa; Mohd Daud Awang; Amini Amir Abdullah; Norlida Mahussin (Human Resource Management Academic Research Society, 2024)
Indexed by ERA